Hidalgo Mendoza,Karelys Edith(2023)Capacidad remediadora del carbón activado y Salix babylonica L. (sauce llorón) en suelos contaminados con cadmio a nivel de vivero.Quevedo.UTEQ.69p. - Hidalgo Mendoza , Karelys Edith (2023)
Cadmium is a metal present in agricultural soils which generates some problems for cocoa production, since it is capable of absorbing the cadmium present through its roots which is responsible for distributing it through the plant including stem, leaves and especially in its fruit, this generates the discrediting of the product since it is harmful to human health. There are different studies that refer that there are forest plants that are capable of absorbing heavy metals from the soil; S. babylonica L. is a forest species that has the bioremediation capacity to absorb heavy metals as well as activated carbon. In the present investigation, three treatments were experimented: T1: soil+ plant, T2: activated charcoal + soil, T3: activated charcoal + soil+ plant. The activated carbon was made from rice husks at a particle size of 500 µ; temperature 500 °C; time 3 hours. Thus, by means of laboratory analysis of soil and plants, treatment 3 gave the best result, 0,42 mg/kg of cadmium at the end of the study compared to 0,51 mg/kg of cadmium at the beginning of the study.